PELATIHAN KOMPUTERISASI DATA REKAM MEDIS MENGGUNAKAN PROGRAM VISUAL FOXPRO-9 PADA KLINIK ANDURING PADANG - Syamsul Kamal; Yuli Mardi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The training activities are based on the staff of medical records in this Anduring Clinic, in terms of data processing and making reports still using a computer manually, namely making letters, typing and making reports using Microsoft Excel, while in terms of computerized data processing there is no or still being done manually, so the computers in this clinic are only used as far as typing and reporting. The purpose of this activity is carried out to improve medical record staff in their skills and expertise, in processing and processing patient data, doctor data, disease data and patient history data and making reports desired by the Anduring clinic, so that the data can be processed and made in a manner quickly and precisely to those who need information. This activity was carried out for one day with 9 participants, including general staff and doctors. The method used is training accompanied by lectures, demonstrations, hands-on practice in front of the computer. The results of the training showed that the medical record staff was able to use and practice the Medical Record Data Compuerization (KDRM) application program in terms of data processing and medical record reporting in the clinic. With this training, it shows that there is a significant influence in training computerized medical record data on improving performance and time efficiency in the processing of data and medical record reports at the clinic.